The impact of coworker support and organizational embeddedness on turnover intention among restaurant employees. Issue 3 (3rd July 2019) - Self, Timothy T.; Gordon, Susan
Abstract: The hospitality industry continues to thrive, but high rates of turnover still persist within line level employees. Drawing from coworker support and organizational embeddedness, it is hypothesized that when employees with more coworker support will decrease their turnover intention. Results from surveying 564 line level employees from a large restaurant chain, indicate that coworker support has an impact on turnover intentions and that employees with more coworker support will have higher levels of organizational embeddedness. The findings highlight the importance of coworker support and organizational embeddedness to reduce turnover intention among line level employees.